How do they add up? The interaction between the placebo and treatment effect: A systematic review. Issue 8 (2nd May 2022) - Boussageon, Rémy; Howick, Jeremy; Baron, Raphael; Naudet, Florian; Falissard, Bruno; Harika‐Germaneau, Ghina; Wassouf, Issa; Gueyffier, François; Jaafari, Nemat; Blanchard, Clara
Abstract : Aim: The placebo effect and the specific effect are often thought to add up (additive model). Whether additivity holds can dramatically influence the external validity of a trial. This assumption of additivity was tested by Kleijnen et al in 1994 but the data produced since then have not been synthetized. In this review, we aimed to systematically review the literature to determine whether additivity held. Methods: We searched Medline and PsychInfo up to 10 January 2019. Studies using the balanced placebo design (BPD), testing two different strengths of placebos, were included. The presence of interaction was evaluated by comparing each group in the BPD with analysis of variance or covariance. Results: Thirty studies were included and the overall risk of bias was high: four found evidence of additivity and 16 studies found evidence of interaction (seven had evidence of positive additivity). Conclusion: Evidence of additivity between placebo and specific features of treatments was rare in included studies. We suggest interventions for placebo‐sensitive ailments should be tested in trials designed to take interactions seriously once an exploratory RCTs has proven their efficacy with sufficient internal validity. Abstract :